Seroprevalence of Japanese encephalitis amongst cases of acute encephalitis syndrome in a tertiary care centre of north east India: a four year retrospective study - Mohan, Daiji G.; Gogoi, Mayuri; Sharma, Ajanta (International Journal of Research in Medical Sciences, 2019)
Background: The present study was undertaken to investigate the trend of JE and the different parameters associated with it. Methods: It was a hospital-based retrospective study conducted from January 2014 to December 2017. A total of 3531 consecutive non-repetitive patients, satisfying the clinical case definition of AES as per the WHO guidelines, were included in the study. Cerebrospinal fluid (CSF) and serum samples were tested for JEV-specific IgM antibodies by the NIV JE IgM Capture ELISA Kit. Results: Of the 3531 patients admitted, 838(23.7%) cases were positive for JE IgM antibodies. There was a significant reduction in the JE positivity rate from 32.9% in 2014 to 13.3% in 2017. The male-to-female ratio was 1.6:1. JE positivity rate was significantly higher in adults as compared to children. The majority of cases occurred during the monsoon and post-monsoon season. Fever (100%), change in mental status (87.8%), headache (70.5%), neck rigidity (32.4%), unconsciousness (35.4%), seizure (43.9%) and paralysis (5%) were the major clinical symptoms. JE positivity was seen to be higher in the rural areas of Assam. Conclusions: A declining trend of JE was seen in this study, however further research work needs to be done to look for non-JE causes of AES.